The Jurisprudential Methods of Sheikh Ma'ruf al-Nawdhi in Explaining the Qatr al-'Aridh System in the Science of Inheritance Laws A Research Paper Prepared by - Salehi, Asst.Prof.Dr.Arkan Haider Omar (Sulaimani Journal for Humanities, 2024)
Praise be to God, and peace and blessings be upon our Prophet Muhammad, his family, his companions, and all who follow him. The learned Sheikh Ma'ruf al-Nawdhi is considered one of the eminent scholars who excelled in both Islamic jurisprudence and modern Islamic law. Through our study of the personality of this learned scholar and some of the abundant insights he left us, interwoven with the sciences of rhetoric and free from error, I was motivated to write about his method of argumentation and deduction. Therefore, I chose the title of this research: "The Jurisprudential Methods of Sheikh Ma'ruf al-Nawdhi in Explaining the Qatr al-'Aridh Poem on the Science of Inheritance." I divided the research into three sections, each with three points, as follows: In the introductory section, I discussed the life of Imam Ma'ruf al-Nawdhi and his jurisprudential methodology. This section comprises two points. In the first point, I discussed the life of Sheikh Ma'ruf al-Nawdhi, and in the second point, I discussed his methodology in the book Qatr al-'Aridh. In the second section, I discussed the Imam's jurisprudential methods in explaining who the heirs are. This section is also divided into two points. In the first point, I discussed... His jurisprudential methods in explaining the inheritance and the reasons for inheritance. In the second section, I mentioned his methods in explaining the heirs and those excluded. As for the third section, I mentioned his methods in explaining the distribution of the inheritance through three sections. In the first section, I mentioned his methods in explaining the inheritance of the agnates. As for the second section, I mentioned his methods in explaining the inheritance of the ascendants. And in the third section, I mentioned his methods in explaining the science of marginalia. Then I mentioned a conclusion to the research with the research results and recommendations, and then an index of sources and references.